The evolution of accessibility surface of China in the high-speed-rail era. (November 2016) - Zhu, Yi; Diao, Mi; Fu, Gang
Numerous studies have investigated the accessibility effect of High Speed Rail (HSR) in China based on projected rail travel time across cities. This study aims to contribute to the literature by visualizing the evolution of the accessibility surface (as measured by economic potential) of China in the HSR era based on real travel time by train between station pairs and analyzing HSR's potential impacts on the spatial disparity of China. We find that the development of HSR has significantly increased the economic potential of Chinese cities. In the meantime, cities with HSR access and cities in the prosperous eastern region benefitted more from the HSR-induced accessibility improvement compared with non-HSR cities and cities in the hinterland. Therefore, instead of contributing to diminishing regional disparity, HSR may lead to greater spatial unevenness in China.